Hygrobot: Hydrogen-Powered Mobile Robotic Platform for Rough Terrain: Electro-Mechanical Design, Physical Implementation, and Experimental Testing - Cirilo Delgado Asencio; Francisca Segura Manzano; José Manuel Andújar Márquez (Applied Sciences)
This work presents the electro-mechanical design, physical implementation, and experimental testing of an intermediate-sized mobile robotic platform, Hygrobot, which is powered by the hybridization of a PEMFC fuel cell and LiPo batteries. Future mobile robots are anticipated to require sustainable and cost-effective energy solutions to increase their working time and adhere to ecological guidelines. Although substantial advancements have been achieved in creating marketable mobile robot designs, including improvements to their physical composition, sensory systems, navigation algorithms, and operational management, their widespread integration is still hindered. This obstacle is mainly attributable to the lack of robust power systems capable of functioning in varied and often unpredictable settings. Hydrogen, as an energy carrier, offers a promising solution to overcome these obstacles. Experimental tests reveal that the Hygrobot platform can achieve a linear speed of 17 km/h, a continuous operating time of over 8 h, and power consumption below 324 WA. Its mechanical design means that Hygrobot is able to overcome obstacles, facilitating movement in the three XYZ axes, and can perform tasks over rough terrain efficiently.